PRINSIP KEADILAN DAN KESEIMBANGAN DALAM PENENTUAN NILAI TUKAR BARANG (HARGA) PERSPEKTIF ISLAM DAN HUKUM PERLINDUNGAN KONSUMEN - Nasyiah, Iffaty (Fakultas Syariah, 2014)
The Law No. 8 of 1999 about Consumer Protection Article 4 letter b said that one of consumer rights, namely the right to select and obtain goods in accordance with the exchange rate. Not found in authentic explanation regarding this exchange rate, if the exchange rate is the exchange rate that is in accordance with the agreement between the seller and the buyer, or in accordance with the production values or the exchange rate that corresponds to the price market, this then raises the question of free interpretation among the businessmen that the exchange rate is determined only by the desire of businessmen and weighing of benefits desired by businesses alone, so that entrepreneurs are allowed to set the exchange rate goods many times from the value of its production. In Islamic law is not found the rules regarding the determination of the limits of this exchange rate, but Islam is a tolerant religion, including in determining the exchange rate as the words of the Prophet Muhammad: